A preparation method and application of betel nut shell activated carbon adsorbent

Through the preparation method of activated carbon suction agent based on betel nut shells, it is difficult to meet the requirements of high load capacity and high adsorption efficiency, and achieve high -efficiency removal of arsenic removal of arsenic wastewater in low arsenic wastewater. It has good adsorption performance and stability.

CN116899547BActive Publication Date: 2025-01-24CENT SOUTH UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311101737.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-01-24
Estimated Expiration
2043-08-29

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove arsenic from low arsenic wastewater, and the traditional activated carbon modification method is difficult to meet the requirements of high load and high adsorption efficiency.

Method used

Adopt the preparation method of activated carbon suction agent based on betel nut shells, and prepare adsorbents with a large ratio and rich pore structure by pre -processing, pre -carbonization, reducing carbonization, and complete carbonization.

Benefits of technology

The efficient adsorption of arsenic has good adsorption performance and stability, and can maintain the ability to remove arsenic at different pH and temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116899547B_ABST
    Figure CN116899547B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an activated carbon adsorbent based on betel nut shell, comprising: (1) pretreatment: washing and drying the betel nut shell, and then rolling the betel nut fiber, soaking the rolled betel nut fiber in an iron sulfate solution, filtering and drying the sample, and then soaking the sample in a magnesium sulfate solution, filtering and drying the sample, and then soaking the sample in ammonia water, filtering, washing, and drying; (2) pre-carbonization: heating the pre-treated product under an inert atmosphere; (3) reduction carbonization: changing the atmosphere to carbon monoxide, and continuing to heat the pre-carbonized product for reduction; (4) carbonization treatment: changing the atmosphere to an inert atmosphere, maintaining the temperature to continue reduction carbonization, and returning to room temperature under an inert atmosphere; (5) product treatment: washing the carbonized product, and drying it to obtain the product. The activated carbon adsorbent based on betel nut shell provided by the invention has excellent adsorption of arsenic in water, and has good application prospects in the field of wastewater purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment and relates to a preparation method and application of a betel nut shell activated carbon adsorbent. Background Art

[0002] Arsenic is a toxic element that has been gradually recognized by the public for its high toxicity. However, in nature, arsenic exists stably in the form of low-toxic insoluble arsenates and sulfides such as realgar, orpiment, and arsenopyrite, and is mainly found in non-ferrous metal ores such as copper, lead, zinc, gold, and silver (Bowell RJ, Alpers CN, Jamieson HE, et al. The environmental geochemistry of arsenic-an overview [J]. Reviews in Mineralogy and Geochemistry, 2014, 79 (1): 1-16.). In recent years, with the continuous development of mineral resources by humans, the low-toxic arsenic that is stable in minerals has been destroyed, causing arsenic to be released in the form of highly toxic water-soluble arsenic such as sulfides, oxides, arsenites, and arsenates. With the continuous progress of science and technology, the research system of high arsenic wastewater has been gradually improved, and the treatment of high arsenic wastewater has achieved remarkable results. However, the arsenic content of the treated liquid is still higher than the national standard of 0.5 mg / L (local standards are more stringent, mostly 0.1 mg / L), which belongs to low arsenic wastewater (Wei Lianghong, Zhou Wenqin. Arsenic Mineral Resource Development and Environmental Governance [J]. Land and Resources Guide, 1992, (3): 259-262.). At present, the accumulation of low arsenic wastewater is becoming more and more serious. How to efficiently remove arsenic from low arsenic wastewater has become an urgent problem.

[0003] There are many studies on low-arsenic wastewater treatment methods, mainly including precipitation, adsorption, ion exchange, membrane separation, phytoremediation, etc. (Pookrod P, Haller KJ, Scamehorn JF. Removal of arsenic anions from water using polyelectrolyte-enhanced ultrafiltration [J]. Separation Science and Technology, 2005, 39 (4): 811-831.). Chemical precipitation methods include neutralization precipitation, flocculation precipitation, etc. When treating low-arsenic wastewater with such methods, it is usually necessary to add excessive arsenic precipitation agents or coagulants to enhance arsenic removal, and it is difficult to meet national discharge or reuse standards. The arsenic concentration in the treated liquid is still higher than 0.5 mg / L; ion exchange is to remove arsenic using ion-specific resins. This process has strong adaptability to the pH of the solution, but the ion exchange method is costly and requires high-cost operation and maintenance. Membrane separation is a method of selectively permeating arsenic using a special membrane. It has high removal efficiency and does not produce toxic solid waste, but it is costly and easy to produce toxic waste. Phytoremediation has the advantages of being environmentally friendly and low-cost, but it has disadvantages such as a long treatment cycle and difficulty in treating arsenic in harvested plants (Lv Jinfang, Quan Yingcong, Tong Xiong. Purification and treatment technology of arsenic-containing wastewater from mining and smelting [J]. Mineral Conservation and Utilization, 2021, 41(01): 53-60.). Adsorption is a relatively mature and simple wastewater treatment technology, especially suitable for water treatment systems with large treatment volume and low concentration. This method is expected to become the main treatment method for low-arsenic wastewater (Gi11es Greg, Mathis Jenn. Using Advanced Adsorptiove Media for Arsenic Treatment [J]. Water Engineering & Management, 2002, 149: 33-37.).

[0004] Common adsorption materials mainly include activated carbon, iron oxide, zeolite, activated alumina, etc. Among them, activated carbon is often used as an adsorption material due to its advantages such as wide source, low cost, developed internal pores, and large specific surface area. Studies have found that in addition to physical adsorption with poor selectivity, activated carbon contains certain oxygen and hydrogen functional groups on the surface and in the pores of activated carbon, such as hydroxyl, carboxyl, phenolic, lactone, ether, etc. These surface functional groups can chemically adsorb with the adsorbent (Burton ED, Bush RT, Johnston SG, et al. Sorption of arsenic (V) and arsenic (III) to schwertmannite [J]. Environmental Science & Technology, 2009, 43 (24): 9202-9207.). Although activated carbon is cheap and easy to obtain, due to its shortcomings such as small pore volume, high ash content, poor adsorption selectivity, and too wide micropore distribution, the adsorption effect of activated carbon on arsenic in sewage is not ideal and cannot meet the current standard requirements. Therefore, the research hotspot and difficulty of arsenic removal by adsorption lies in the modification of traditional activated carbon adsorbents to improve the arsenic removal capacity.

[0005] In the prior art, conventional activated carbon is modified to effectively improve the physical structure characteristics and chemical properties of activated carbon, in order to improve its selectivity and adsorption effect on arsenic. Activated carbon modification methods can be mainly divided into oxidation modification, reduction modification, load modification and electrochemical modification (Song Xiaolan, Liu Hongyan, Cheng Lei, et al. Surface modification of coconut-based activated carbon by liquid-phase oxidation and its effects on lead ion adsorption [J]. Desalination, 2010, 255 (1-3): 78-83.). Oxidation / reduction modification is to introduce or remove certain functional groups in a targeted manner by changing the surface acidity / alkalinity of activated carbon, so that activated carbon has special adsorption properties; load modification is to load iron, aluminum and manganese metals or metal oxides on the surface of activated carbon first, and use their strong binding force to arsenic to promote the adsorption of arsenic by activated carbon; electrochemical modification is to use a micro-electric field to change the charge and chemical properties of the surface of activated carbon, thereby improving its adsorption selectivity and adsorption performance. The above modification methods can improve the selectivity and adsorption effect of activated carbon for arsenic by changing the microporous structure of the activated carbon surface, changing the properties of the functional groups on the activated carbon surface, or increasing the potential on the activated carbon. However, it is difficult to meet the requirements of high arsenic loading and high adsorption efficiency of activated carbon by using a single modification method (Velazqerz H, Arcibar A, Rangel R. Overview of As(V) adsorption on Zr-functionalized activated carbon foraqueous streams remediation[J]. Journal of Environmental Management, 2018, 212: 121-130.).

[0006] Chinese patent CN 201810682691.6 discloses a composite adsorbent for flue gas from incineration of domestic waste, wherein the raw materials of the adsorbent include the following components by weight: 30-35 parts of coconut shell charcoal, 20-22 parts of shell powder, 15-18 parts of sodium bentonite, 12-15 parts of fly ash, 10-12 parts of modified ferroferric oxide, 12-15 parts of diatomaceous earth, 6-8 parts of bamboo charcoal fiber, 8-10 parts of vermiculite powder, 6-8 parts of expanded graphite, 5-8 parts of sepiolite powder, 1-3 parts of talc, 1-1.5 parts of magnesium oxide, and 2-4 parts of aluminum oxide. The raw materials are mixed by physical mixing, which is not fully mixed, reducing the adsorption effect, and does not involve the specific adsorption of arsenic (V). Summary of the invention

[0007] In view of the technical problem that a single modification method used in the prior art is difficult to meet the requirements of high arsenic loading and high adsorption efficiency of activated carbon, and that the raw materials are mixed in a physical mixing manner, the mixing is insufficient, thereby reducing the adsorption effect, the purpose of the present invention is to provide a preparation method and application of an activated carbon adsorbent based on betel nut shell.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] The present invention provides a method for preparing a betel nut shell activated carbon adsorbent, comprising the following steps:

[0010] (1) Pretreatment: Wash and dry the betel nut shell, and then crush it. Then, soak the crushed betel nut fiber in an iron sulfate solution. After filtering and drying, soak the sample in a magnesium sulfate solution. After filtering and drying, soak the sample in ammonia water. After filtering, washing, and drying, obtain a pretreated product.

[0011] (2) Pre-carbonization: placing the pre-treated product obtained in step (1) under an inert atmosphere for heating to obtain a pre-carbonized product;

[0012] (3) Reduction carbonization: changing the atmosphere to carbon monoxide, and further heating the pre-carbonized product obtained in step (2) to reduce it, thereby obtaining a reduction carbonized product;

[0013] (4) Carbonization treatment: changing the atmosphere to an inert atmosphere, maintaining the temperature to continue the reduction carbonization, and returning to room temperature under the inert atmosphere to obtain a carbonized product;

[0014] (5) Product processing: The carbonized product obtained in step (4) is washed and dried to obtain an adsorbent product.

[0015] In a preferred embodiment, in step (1), the concentration of the ferric sulfate solution is 5 to 10 mol / L, and the crushed betel nut fibers are soaked in the ferric sulfate solution for 24 to 48 hours.

[0016] In a preferred embodiment, in step (1), the solubility of the magnesium sulfate solution is 1 to 3 mol / L, and the sample is immersed in the magnesium sulfate solution for 24 to 48 hours.

[0017] In a preferred embodiment, in step (1), the ammonia water content is 25-28%, and the sample is placed in the ammonia water for neutralization and soaking for 12-24 hours.

[0018] In a preferred embodiment, in step (2), the pretreated product is placed in a nitrogen atmosphere for heating treatment, the heating temperature is 500-550° C., and the insulation time is 60-90 min.

[0019] In a preferred embodiment, in step (2), a tubular furnace is used for heating treatment, and the heating rate of the tubular furnace is 1 to 3° C. / min.

[0020] In a preferred embodiment, in step (3), the pre-carbonized product is further heated to 600-650° C. for reduction for 30-60 minutes.

[0021] In a preferred embodiment, in step (4), the atmosphere is changed to nitrogen, the temperature is maintained and the firing is continued for 120 to 180 minutes, and then the temperature is restored to room temperature under a nitrogen atmosphere.

[0022] In a preferred embodiment, in step (5), the carbonized product is washed with 50% ethanol and then washed with distilled water until neutral.

[0023] An activated carbon adsorbent based on betel nut shell is prepared by the above method.

[0024] The activated carbon adsorbent has a specific surface area of ​​700 to 800 cm 3 , average pore diameter 2.71nm.

[0025] The invention also provides application of the activated carbon adsorbent in treating arsenic-containing wastewater.

[0026] Principle of the present invention:

[0027] The present invention uses betel nut shell as raw material, and pre-treats Fe 3+ Mg 2+ Impregnated into the fiber structure of betel nut shell, and then neutralized with ammonia to make Fe 3+ Mg 2+ The betel nut shell after pre-carbonization can achieve partial carbonization of the betel nut shell, and at the same time, the iron hydroxide and magnesium hydroxide entering the fiber structure of the betel nut can be decomposed into iron oxide and magnesium oxide (the complete decomposition temperature of iron hydroxide is lower than 500°C, and the complete decomposition temperature of magnesium hydroxide is 350°C). In addition, the byproduct ammonium sulfate can also be decomposed into ammonia, nitrogen, sulfur dioxide and water under this condition (the complete decomposition temperature of ammonium sulfate is 513°C); the pre-carbonized betel nut shell is reduced and carbonized in a carbon monoxide atmosphere (600-650°C). During this process, ferric oxide is reduced to ferric oxide by carbon monoxide, while magnesium oxide does not react with carbon monoxide; the reduced carbonized betel nut shell is finally carbonized in a nitrogen atmosphere (600-650°C); the carbonized product is washed with ethanol and distilled water to obtain the adsorbent product. The method was used to successfully prepare an activated carbon adsorbent based on betel nut shell, which has good adsorption performance for arsenic. The reaction equations of each stage are as follows:

[0028] (1) Pretreatment process:

[0029]

[0030] Fe 3+ +3OH=Fe(OH)3↓ (2)

[0031] Mg 2+ +2OH - =Mg(OH)2↓ (3)

[0032] 3(NH4)2SO4=3SO2↑+6H2O↑+4NH3↑+N2↑ (4)

[0033] (2) Pre-carbonization process:

[0034] 2Fe(OH)3=Fe2O3+3H2O↑ (5)

[0035] Mg(OH)2=MgO+H2O↑ (6)

[0036] (C6H 10 O5) n =6nC+5nH2O↑ (7)

[0037] C+H2O(g)=CO+H2 (8)

[0038] (3) Reduction carbonization process:

[0039] 3Fe2O3+CO=2Fe3O4+CO2 (9)

[0040] (C6H 10 O5) n =6nC+5nH2O (10)

[0041] C+H2O(g)=CO+H2 (11)

[0042] (4) Complete carbonization process:

[0043] (C6H 10 O5) n =6nC+5nH2O (12)

[0044] C+H2O(g)=CO+H2 (13)

[0045] The invention adopts cheap betel nut shell as raw material to prepare arsenic removal adsorbent through a synergistic modification method, combines the advantages of various modification methods, specifically changes or strengthens the adsorption performance of the adsorbent for arsenic (V), and simultaneously improves the strong selectivity and high adsorption capacity of the adsorbent for arsenic (V).

[0046] The invention adopts betel nut shell as raw material, which is low in price, and has simple synthesis method and convenient operation, thus providing a new option for the treatment of arsenic-containing wastewater.

[0047] Compared with the existing technology, the present invention has the following beneficial effects:

[0048] (1) The present invention uses cheap betel nut shells as raw materials to prepare the betel nut shell-based activated carbon adsorbent, which has a large specific surface area and rich pore structure, can provide more adsorption sites for arsenic adsorption, and achieve efficient arsenic adsorption. At the same time, the unique magnetic properties and the synergistic effect of iron arsenate and magnesium arsenate precipitation improve the arsenic removal performance of the material.

[0049] (2) The synthesis method of the betel nut shell-based activated carbon adsorbent synthesized by the present invention is simple and easy to operate.

[0050] (3) The betel nut shell activated carbon adsorbent provided by the present invention has high stability and good adsorption performance during the adsorption process.

[0051] (4) The betel nut shell activated carbon adsorbent provided by the present invention has excellent adsorption capacity for arsenic in water and has good application prospects in the field of wastewater purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings and appendices required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0053] Figure 1 A technical roadmap for preparing the betel nut shell-based activated carbon adsorbent of the present invention;

[0054] Figure 2 This is a SEM image of the betel nut shell activated carbon adsorbent of Example 1;

[0055] Figure 3 The adsorption capacity of the adsorbent material provided in Example 1 under As(V) solution conditions of different pH and initial concentrations;

[0056] Figure 4 The adsorption capacity of the adsorbent material provided in Example 1 changes with time under different temperature conditions. DETAILED DESCRIPTION

[0057] The following are specific implementation cases given by the inventor. It should be noted that these embodiments are only for better interpretation of the present invention and are not intended to limit the scope of implementation of the present invention. All parameter selections within the scope of the technical solution of the present invention belong to the scope of protection of the present invention.

[0058] The following is further described through specific embodiments and drawings.

[0059] Example 1

[0060] The betel nut shell is crushed to expose the fiber fully. The crushed betel nut fiber is soaked in 8mol / L iron sulfate solution for 24h, filtered and dried at room temperature, and the dried sample is soaked in 2mol / L magnesium sulfate solution for 24h. The sample is filtered and dried at room temperature and then placed in 25% ammonia water for neutralization and soaking for 12h. The neutralized sample is filtered, washed, and dried at room temperature for use. The pretreated sample is placed in a tube furnace at 500℃ (heating rate 3℃ / min) and kept warm for 90min in a nitrogen atmosphere to obtain a pre-carbonized product; then the atmosphere is changed to carbon monoxide, and the temperature is continued to rise to 650℃ (heating rate 3℃ / min) and fired for 30min to obtain a reduction carbonized product; finally, the temperature is kept under nitrogen atmosphere for 120min, and the temperature is cooled to room temperature under nitrogen atmosphere. The carbonized sample is washed with 50% ethanol solution-distilled water until neutral, and dried at room temperature to obtain an activated carbon adsorbent based on betel nut shell, and the adsorbent is stored in a dryer.

[0061] Figure 2 This is the SEM image of the betel nut shell activated carbon adsorbent according to Example 1. Figure 2 It can be seen that the betel nut shell-based activated carbon adsorbent is fibrous, has a rich pore structure, and has a high specific surface area, which can create favorable conditions for the removal of arsenic.

[0062] Example 2

[0063] The betel nut shell is crushed to expose the fiber fully. The crushed betel nut fiber is soaked in 10mol / L iron sulfate solution for 48h, filtered and dried at room temperature, and the dried sample is soaked in 3mol / L magnesium sulfate solution for 48h. The sample is filtered and dried at room temperature and then placed in 25% ammonia water for neutralization and soaking for 24h. The neutralized sample is filtered, washed, and dried at room temperature for use. The pretreated sample is placed in a tube furnace at 520℃ (heating rate 3℃ / min) and kept warm for 60min in a nitrogen atmosphere to obtain a pre-carbonized product; then the atmosphere is changed to carbon monoxide, and the temperature is continued to rise to 600℃ (heating rate 3℃ / min) and fired for 60min to obtain a reduction carbonized product; finally, the temperature is kept under nitrogen atmosphere for 180min, and the temperature is cooled to room temperature under nitrogen atmosphere. The carbonized sample is washed with 50% ethanol solution-distilled water until neutral, and dried at room temperature to obtain an activated carbon adsorbent based on betel nut shell, and the adsorbent is stored in a dryer.

[0064] Example 3

[0065] The adsorbent is the material prepared in Example 1, and the adsorption performance and adsorption kinetics of the adsorbent synthesized by the present invention on arsenic are studied.

[0066] (1) Adsorption performance study

[0067] The initial solution was prepared as 1, 5, 10, 20, 50, 75, 100, 200, 350 mg / L As(V) solution, 100 mL was taken and added to 9 250 mL conical flasks, and the pH value of the As(V) solution was adjusted to 4 and 7 with 0.1 mol / L NaOH and H2SO4 solution, and 0.1 g of adsorbent material was added to the conical flasks respectively to keep the adsorbent concentration in the solution at 1 g / L. The conical flasks were sealed with plastic wrap to prevent the solution from splashing during the shaking process, and the conical flasks were placed in a constant temperature oscillator at 25 ° C and shaken at 150 rpm for 12 hours. After adsorption, vacuum filtration was used to achieve solid-liquid separation, and the solution was analyzed by inductively coupled plasma emission spectrometry (ICP-AES) to analyze the concentration of As(V) in the adsorbed solution, and the adsorption capacity and adsorption rate of the material were calculated.

[0068] By measuring, under different initial concentrations of As(V) solution, the adsorption amount and removal efficiency of the adsorbent material provided in Example 1 for As(V) solution are as follows: Figure 3As shown, the initial As(V) concentrations of the betel nut shell activated carbon adsorbent at pH = 4 and 7 were 1, 5, 10, 20, 35, 50, 75, 100, and 150 mg / L As(V) solutions, respectively. At pH = 4, the equilibrium adsorption amounts of As(V) by the adsorbent were 0.6714 mg / g, 3.57111 mg / g, 7.1396 mg / g, 14.1266 mg / g, 23.0950 mg / g, 30.5643 mg / g, 40.6001 mg / g, 49.03571 mg / g, and 59.54286 mg / g, respectively, indicating that the adsorbent material has good adsorption performance for As(V). The Langmuri model fitting results show that the adsorption amount can reach more than 114.39 mg / g.

[0069] (2) Study on adsorption kinetics

[0070] 100 mL of As(V) solution with an initial concentration of 50 mg / L was taken in a conical flask and the pH of the solution was adjusted to 4. 0.1 g of adsorbent material was added to the conical flask to maintain the adsorbent concentration in the solution at 1 g / L. The adsorption kinetics under different temperature conditions (25, 35, 45 ° C) were investigated. The conical flask was sealed with plastic wrap to prevent the solution from splashing during the shaking process. The conical flask was placed in a desktop constant temperature oscillator at 25 ° C and shaken at 150 rpm at (5 min, 15 min, 30 min, 45 min, 1 h, 2 h, 3 h, 4 h, 6 h, 8 h, 10 h, 12 h, 15 h, 18 h, 21 h, 24 h) time points. After adsorption, vacuum filtration was used to achieve solid-liquid separation. The solution was analyzed by inductively coupled plasma emission spectrometry (ICP-AES) to analyze the concentration of As(V) in the adsorbed solution, and the adsorption capacity of the material was calculated.

[0071] Figure 4 The following is a graph showing the variation of the adsorption amount of the adsorbent material provided in Example 1 at two different temperatures and initial arsenic concentrations over time. Figure 4 It can be seen that within 0.5 hours after the adsorption, the adsorption material adsorbed As(V) very quickly, and the adsorption capacity increased rapidly. After that, the adsorption capacity increased slowly, and the adsorption amount basically reached a balance state after 8 hours, indicating that the material has a strong affinity for As(V) and a fast adsorption rate for As(V).

[0072] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing an activated carbon adsorbent based on betel nut shell, characterized in that: The following steps are involved: (1) Pretreatment: The betel nut shell is washed and dried, and then crushed. The crushed betel nut fiber is soaked in an iron sulfate solution. After filtering and drying, the sample is soaked in a magnesium sulfate solution. After filtering and drying, the sample is soaked in ammonia water. After filtering, washing and drying, a pretreated product is obtained. (2) Pre-carbonization: placing the pre-treated product obtained in step (1) under an inert atmosphere for heating to obtain a pre-carbonized product; (3) Reduction carbonization: changing the atmosphere to carbon monoxide, and further heating the pre-carbonized product obtained in step (2) to reduce it, thereby obtaining a reduction carbonized product; (4) Carbonization treatment: Change the atmosphere to an inert atmosphere, maintain the temperature to continue the reduction carbonization, and return to room temperature under the inert atmosphere to obtain the carbonized product; (5) Product processing: washing and drying the carbonized product obtained in step (4) to obtain an adsorbent product; In step (1), the concentration of the ferric sulfate solution is 5-10 mol / L, and the crushed betel nut fiber is immersed in the ferric sulfate solution for 24-48 hours; In step (1), the solubility of the magnesium sulfate solution is 1-3 mol / L, and the sample is immersed in the magnesium sulfate solution for 24-48 hours; In step (2), the pretreated product is placed in a nitrogen atmosphere for heating treatment at a temperature of 500-550° C. for a holding time of 60-90 min; In step (3), the pre-carbonized product is further heated to 600-650° C. for reduction for 30-60 min.

2. A method for preparing an activated carbon adsorbent based on betel nut shell according to claim 1, characterized in that: In step (1), the ammonia water content is 25-28%, and the sample is placed in the ammonia water for neutralization and soaking for 12-24 hours.

3. A method for preparing an activated carbon adsorbent based on betel nut shell according to claim 1, characterized in that: In step (2), a tubular furnace is used for heating treatment, and the heating rate of the tubular furnace is 1-3°C / min.

4. A method for preparing an activated carbon adsorbent based on betel nut shell according to claim 1, characterized in that: In step (4), the atmosphere is changed to nitrogen, the temperature is maintained and the firing is continued for 120 to 180 minutes, and then the temperature is restored to room temperature under the nitrogen atmosphere.

5. An activated carbon adsorbent based on betel nut shell, characterized in that: The method is prepared according to any one of claims 1 to 4.

6. Use of the betel nut shell activated carbon adsorbent according to claim 5 in the treatment of arsenic-containing wastewater.

Citation Information

Patent Citations

  • Composite adsorbent for domestic waste incineration flue gas and preparation method thereof

    CN108837802A

  • Composite biological carbon material loading iron oxide as well as preparation method and application of composite biological carbon material

    CN104587958A

  • Method for preparing activated carbon using betel nut shells as raw materials and prepared activated carbon

    CN104803384A

  • Porous carbon adsorbent as well as preparation method and application thereof

    CN105251445A

  • Preparation method of bagasse charcoal and magnesium-iron hydrotalcite composite adsorbent

    CN106311138A